Decabromodiphenyl ethane, a flame retardant, acts as a thyroid hormone receptor antagonist - Choi, Soocheol; Cho, Hyunki; Karim, Md Adnan; Park, Chang Gyun; Yoon, Juyoung; Kim, Young Jun; Ryu, Chang Seon (Toxicological research, 2026)
Flame retardants are integral components in numerous consumer and industrial products. Accumulating research has shown that retardants disrupt the endocrine system via the modulation of thyroid hormone receptors (THRs). To investigate the mechanisms underlying this effect, we established a luciferase reporter assay system using HEK293 cells expressing the human THR isomers THRα and THRβ, and screened six flame-retardant compounds with agonistic or antagonistic activity. We examined THR agonism or antagonism in these compounds, which included organophosphate (tris(3-chloropropyl) phosphate), bisphenol-type (tetrabromobisphenol A), and brominated compounds (decabromodiphenyl ethane [DBDPEthane], decabromodiphenyl ether [DBDPEther], 1,2-bis(2,4,6-tribromophenoxy) ethane, and DC604). Among these, DBDPEthane, a widely used flame retardant, has emerged as a potential endocrine-disrupting chemical. The structurally related compounds DBDPEther and DBDPEthane were found to exert antagonistic effects on both THRα and THRβ. To elucidate the molecular basis of this antagonism, molecular docking analysis was performed using the ligand-binding domains of THRα and THRβ. The results indicated binding of DBDPEthane within ligand-binding pockets of both THRα and THRβ, forming specific hydrogen bonds and hydrophobic interactions that may support its antagonistic effects. To further characterize the dynamic interactions between DBDPEthane and THRα or THRβ, we conducted molecular dynamics simulations, using the root mean square deviation (RMSD), root mean square fluctuation (RMSF), and solvent-accessible surface area (SASA) as metrics. The results revealed distinct binding stability and conformational flexibility between DBDPEthane and THRβ, supported by RMSD, RMSF and SASA. These findings highlight the potential of DBDPEthane to antagonize both THRα and THRβ, providing functional and structural insights into its thyroid-disrupting properties in the context of receptor subtype selectivity.
Online verfügbar: 08. September 2025
Gesehen am 19.01.2025